2009
DOI: 10.1007/s12149-009-0230-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of carbon-11 choline PET/CT in the management of uterine carcinoma: initial experience

Abstract: (11)C-choline PET/CT is an accurate means for the management of patients with uterine carcinoma. The combination of (11)C-choline PET/CT and MRI increases the accuracy of staging in patients with uterine carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Thus, for detection of gynecologic malignancies 11 C-choline might be superior to 18 F-FDG and 18 F-FLT, which are excreted via the urinary tract, because of reduced masking of the pelvic region. 25,26 In this study, the clinical gold standard in PET oncology, 18 F-FDG, showed a markedly increased uptake into the tumor tissue of rabbits, whereas 18 F-FLT failed. However, 11 C-choline revealed an uptake comparable to 18 F-FDG, thus representing an alternative PET tracer to 18 F-FDG for imaging papillomavirus-induced tumors.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Thus, for detection of gynecologic malignancies 11 C-choline might be superior to 18 F-FDG and 18 F-FLT, which are excreted via the urinary tract, because of reduced masking of the pelvic region. 25,26 In this study, the clinical gold standard in PET oncology, 18 F-FDG, showed a markedly increased uptake into the tumor tissue of rabbits, whereas 18 F-FLT failed. However, 11 C-choline revealed an uptake comparable to 18 F-FDG, thus representing an alternative PET tracer to 18 F-FDG for imaging papillomavirus-induced tumors.…”
mentioning
confidence: 64%
“…35,36 Indeed 11 C-choline has been used successfully in PET imaging of tumors in the pelvic region, including cervical cancer. [22][23][24]26,37,38 Therefore, the simultaneous use of noninvasive, high-tissue contrast MR imaging in combination with 11 C-choline PET has the potential to improve diagnosis and support future clinical staging of cancers. In addition, we confirmed reports from previous studies demonstrating that the uptake of 11 C-choline into tumors was lower than the uptake of 18 F-FDG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that carbon-11 choline PET/CT was good for tumor, nodal and metastatic saging, as well as SUV reduction was remarkable in five patients after receiving treatment. [100] FDG-PET has been evaluated for treatment planning in cervical cancer patients. Grigsby et al evaluated patients with cervical cancer and negative lymph nodes diagnosed by FDG-PET.…”
Section: Cervical Cancermentioning
confidence: 99%
“…In cell line studies of endometrial cancer, the expression and activity of choline kinase alpha is increased with a several-fold increase in the uptake of 3 H choline in endometrial cancer cells compared to normal endometrial stromal cells (19). Early pilot studies of 11 C choline in gynecological cancer show promise (20,21), however 18 F-labelled fluoro-methyl and fluoroethyl choline have a longer radioactive half-life (110 minutes) and are therefore more practical to use. The use of Fluoro-ethyl-choline (FEC)-PET/CT in detecting nodal metastases in endometrial and cervical cancer has not been previously explored.…”
Section: Introductionmentioning
confidence: 99%